Model minority stereotypes of Asian American women in American media: perceptions and influences among women of diverse racial-ethnic backgrounds - Wu, Yue (Kansas State University, 2010)
This study examines women’s interpretations of model minority stereotypes of Asian American women in prime-time television. This stereotype depicts Asian Americans as well educated, intelligent, competitive, hardworking and successful career women. Using focus group discussions, this study recalls perceptions and explores potential effects of model minority stereotypes in prime-time television among women of varied racial-ethnic backgrounds. The study finds that both Asian/Asian American women and women from other racial-ethnic groups confirm belief in the model minority media stereotype in prime-time television. The selfperception and others’ perception of Asian American women as a model minority imposes stress on Asian/Asian American women in terms of gender role, academic performance and career achievement. Additionally, perceptions toward the model minority media stereotype among women of varied racial-ethnic backgrounds influence intergroup relations, interracial contact and evaluation of the model minority media image. Implications indicate that the model minority media stereotype has both positive and negative influences on Asian/Asian American women and other racial-ethnic groups. The study suggests that American media can increase the frequency and diversity of Asian American women’s media representation to reduce the negative societal influence of one-dimensional media stereotypes.
Keywords: the model minority stereotype; racial-ethnic background; focus group; Asian American women; prime-time television; racial perceptions; Mass Communications (0708); Sociology, Ethnic and Racial Studies (0631); Women's Studies (0453)